The Big Peter Rabbit book things to do, games to play, stories, presents to make - Potter, Beatrix 1866-1943. (Harmondsworth, Middlesex, Eng New York F. Warner Viking Penguin, 1986)
An activity book with stories of Beatrix Potter and related activities, games, recipes, and handicraft.
Keywords: Potter, Beatrix -- 1866-1943 -- Juvenile literature; Literary recreations -- Juvenile literature; Amusements -- Juvenile literature; Amusements; Games; Handicraft; Short stories